Museu de Brinquedos: lugar de memórias, culturas e encantamentos - Santiago, Mariani Guedes (2017)
Physical education is an area that allows studies on different subjects. Here we choose the theme toy and game, traditional and popular, from the analysis of the Popular Toy Museum, located in Natal, Rio Grande do Norte, taking into account its history. In addition to understanding the functioning and organization, we seek to know and analyze the understanding adopted by the institution on popular and traditional game and toy; and to identify and discuss possible relationships between the museum and physical education. We understand that toys and games, popular and traditional, are part of the culture, however, due to social changes, many are not remembered, and thus fail to tell their story and propagate their cultural specificity. The museums of games and toys, in the Brazilian context, have little visibility. In Brazil there are approximately eight specific museums of games and toys. The museum, to a large extent, is a place that contemplates the past, brings it to the present and leads it into the future. In the museum of games and toys, where the world of make-up prevails, all times can be remembered, lived, known, in one place, where all this magic is not reduced to contemplation and observation. Apart from a place of memory, the museum can also be a place to play and have fun. To assist in the understanding of the game and toy are mainstays among other authors: Johan Huizinga, Roger Caillois, Daniil Elkonin, Tizuco Kishimoto, Gilles Brougère. To achieve the research, a field visit was carried out, that is, observations using field diary and interview with the coordinator of the institution and others involved. As a way of analyzing the sources of research, we rely on the theory of Maria Cecília de Souza Minayo and its ways of handling the sources. After spending a week at the Popular Toy Museum, observing its routine, following the visits, talking with the coordinator, knowing and feeling each toy exposed, we were able to know its history and organization and understand the insertion of the Museum in the IFRN. With a background in physical education, the coordinator of the Museum, also a professor of IFRN, is responsible for the administration, organization, maintenance and all the demand coming from the Museum. Two fellows, IFRN students, usually from the Tourism Guide course, accompany the visits. The Museum receives an average of 3 to 4 thousand visits per year, the majority scheduled by public schools in the city of Natal-RN. Regarding the definitions of game and toy, for the Museum coordinator, toy can be understood as instrument of the game, and game a construction that presents rules. After many readings and reflections, we consider games and toys as cultural patrimonies that, due to the diverse conceptualizations and difficulty in arriving at a precise definition, must be described, and can be named only by those who manipulate them, by who gives meaning to the object in that given time. By walking through the spaces of the museum and watch the exposed toys, it was possible to see how physical education was present, a creative physical education, which often ends up being left out, a physical education which are allowed to play and play freely, and not just reproduce concepts and movements.